Experimental electrical characterisation of thermoelectric generator using forced convection water cooling / Raihan Abu Bakar...[et al.] - Abu Bakar, Raihan; Singh, Baljit; Remeli, Muhammad Fairuz (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Thermoelectric Generator (TEG) provides unique advantages as compared to other heat engines as it is capable to convert heat to electricity directly without having any moving parts. Furthermore, TEG is compact, simple and noiseless and requires very minimal maintenance. This paper presents an experimental and analytical study of a model consisting of a TEG located between a copper water cooling jacket and an aluminium block which acts as a heat spreader. The copper water cooling jacket was used in this study as water has higher thermal capacity than air. Besides, copper is one of highest thermal conductivity materials. TEG characterisation in term of electrical was investigated in this study. Based on the result, it shows a linear proportion relationship between open-circuit voltage and temperature difference across TEG. The result also clearly shows the power output of TEG increases as the temperature gradient across TEG increases. In addition, the impact of water flowrate on TEG power output was also studied. Based on the finding, there was an optimum water flowrate of 80 ml/s. Further increasing the water flowrate is not favourable as it will not increase power output and may lead to higher pumping power for water circulation. At this optimum water flowrate, the maximum power output obtained is equal to 530 mW when TEG hot-side temperature (Th) is 180 ℃.